2011
DOI: 10.1371/journal.pone.0024353
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic Neisseria Hitchhike on the Uropod of Human Neutrophils

Abstract: Polymorphonuclear neutrophils (PMNs) are important components of the human innate immune system and are rapidly recruited at the site of bacterial infection. Despite the effective phagocytic activity of PMNs, Neisseria gonorrhoeae infections are characterized by high survival within PMNs. We reveal a novel type IV pilus-mediated adherence of pathogenic Neisseria to the uropod (the rear) of polarized PMNs. The direct pilus-uropod interaction was visualized by scanning electron microscopy and total internal refl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 63 publications
(66 reference statements)
0
22
0
Order By: Relevance
“…It is also possible that VV binds to the uropods of phagocytes such as monocytes, macrophages, and neutrophils in PHLs to not only spread to tissues but also resist phagocytic activity. A recent report has demonstrated that Neisseria meningitidis binds to the uropods of migrating neutrophils to resist neutrophil phagocytic activity and to spread the bacteria during cell migration through epithelial cell layers (45). This report also showed that uropod-bound bacteria were resistant to phagocytosis, which occurs only at the pseudopod end (leading edge) (45).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also possible that VV binds to the uropods of phagocytes such as monocytes, macrophages, and neutrophils in PHLs to not only spread to tissues but also resist phagocytic activity. A recent report has demonstrated that Neisseria meningitidis binds to the uropods of migrating neutrophils to resist neutrophil phagocytic activity and to spread the bacteria during cell migration through epithelial cell layers (45). This report also showed that uropod-bound bacteria were resistant to phagocytosis, which occurs only at the pseudopod end (leading edge) (45).…”
Section: Discussionmentioning
confidence: 99%
“…A recent report has demonstrated that Neisseria meningitidis binds to the uropods of migrating neutrophils to resist neutrophil phagocytic activity and to spread the bacteria during cell migration through epithelial cell layers (45). This report also showed that uropod-bound bacteria were resistant to phagocytosis, which occurs only at the pseudopod end (leading edge) (45). Our results also showed that VV would preferentially bind to the uropod ends of phagocytes, which may also provide protection from phagocytosis and assist in viral dissemination leading to generalized VV infections.…”
Section: Discussionmentioning
confidence: 99%
“…In Neisseria, the large (nonpilin) PilC1 and PilC2 proteins have been reported to act as cell contact-dependent pilus-associated adhesins (384), although the evidence is indirect and therefore somewhat controversial. N. meningitidis isolates use PilC1 and PilC2 to adhere to the uropods of neutrophils in order to escape phagocytosis (362). P. aeruginosa expresses an integrinbinding PilC homolog, called PilY1, that requires the T4P system for surface localization, although its direct association with pili has not yet been demonstrated convincingly (13,53,174,204).…”
Section: Adherence and Aggregationmentioning
confidence: 99%
“…N. meningitidis can bind to and traverse both epithelial and endothelial cell layers, in a T4P-dependent manner (376), and it recruits a variety of host proteins to do its bidding. The bacteria bind to cells and form microcolonies in a manner that requires retractable T4P and the noncore minor pilins PilV and PilX, as well as the pilus-associated PilC1 and PilC2 proteins (63,111,225,283,287,288,362,415).…”
Section: Manipulation Of Host Cellsmentioning
confidence: 99%
“…The result is a weakening of the junctions between epithelial/endothelial cells, which Casellato and colleagues postulate could be at least partly responsible for the increase in endothelial permeability associated with sepsis (Casellato et al, 2014). Given the recent demonstration that N. meningitidis is able to 'hitchhike' by attachment of its TfP to the uropod of human neutrophils (Soderholm, Vielfort, Hultenby, & Aro, 2011), it is biologically plausible that C2-weakened junctions might allow for increased neutrophil extravasation into the nasopharynx, providing more 'traffic' upon which epithelium-localised Neisseria might 'hitch a ride'. Pulled along in relative safety behind the neutrophils, presumably en route to sites of injury, infection or inflammation, the result could be the further dissemination of the meningococcus across the nasopharyngeal surface and 'resettlement' into areas either where the Neisseria can exploit an adaptive advantage (e.g.…”
Section: The Role Of Phase Variationmentioning
confidence: 99%